Clinically significant of drug-drug interactions among children: a review - Ridhayani, Firda; Sari, Ika Puspita; Andayani, Tri Murti (Indonesian Journal of Pharmacology and Therapy, 2024)
Drug-drug interactions among children are a getting along concern in health care settings, specifically intensive care units, as sources of adverse drug events that may affect patient condition. Children admitted to pediatric intensive care unit are more prone to drug-drug interactions owing to the diseases and medications complexity. This condition could put the patient at high risk of harm, particularly with his critical condition, so need intense considerations from clinical practitioners to prevent adverse drug events caused by potential drug-drug interactions. This article’s review attempts to explore the important drug-drug interactions among children, including explaining the drug combination, mechanism, and related adverse drug events to help health practitioners recognize it earlier before prescribing the medication. This article’s review explored previous research results from PubMed and Google Scholar as literature resources and PRISMA flow chart as protocol for article selection process. A total of 9 articles discussed comprehensively about the type of drug combinations, mechanism of drug-drug interactions, and associated adverse drug events with significant drug-drug interactions that commonly occurred in children’s patient during the treatment. The drug-drug interaction including midazolam-phenobarbital, cannabidiol-clobazam, Paxlovid-tacrolimus, inhaled fluticasone propionate-lopinavir/ritonavir, rifampicin-warfarin, clofazimine-moxifloxacin, benzatropine-haloperidol, and enalapril-spironolactone. In conclusion, gaining a better understanding of drug-drug interactions among children will empower healthcare professionals to develop useful strategies to recognize, manage, and prevent various types of pharmacokinetic and pharmacodynamic interactions. Especially at different stages in terms of age, physiology, and complexity of the disease in children.